Role of the AV3V region in the pressor responses induced by amygdala stimulation - (:unkn) unknown (My University, 1997)
The role of the anteroventral third ventricle (AV3V) region in the pressor responses to carbachol injected into the lateral cerebral ventricle (i.c.v.), the electrical stimulation of and carbachol-induced stimulation of, the central nucleus of the amygdala were investigated in conscious, unrestrained Sprague-Dawley rats. I.c.v. and intra-amygdalar carbachol caused a significant rise in blood pressure of 22.9 +/- 2.8 and 16.8 +/- 2.2 mmHg, respectively. Electrical stimulation (1 ms, 80 Hz, 50-300 microA, for 30 s) of the central nucleus of amygdala also produced intensity-dependent pressor effects. Electrolytic lesion of the AV3V region abolished the pressor responses induced by carbachol and by electrical amygdala stimulation. The heart rate changes were also significantly inhibited in the AV3V-lesioned rats. These results indicate that the integrity of the AV3V region is essential for the central cholinergic cardiovascular changes induced by central amygdaloid nucleus stimulation.
Keywords: Female; Animals; Male; Rats; Blood Pressure; Heart Rate; Rats, Sprague-Dawley; Injections, Intraventricular; Cerebral Ventricles; Carbachol; Electric Stimulation; Amygdala; Muscarinic Agonists